Peran Pemerintah Daerah dalam Implementasi Program Kartu Prakerja di Provinsi Jawa Barat - Andina, Elga (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2022)
The Pre-Employment Card Program is a responsive policy due to the difficulty of getting a job, especially during the pandemic. Subnational governments are expected to play roles in (1) socialization; (2) provision of data on training institutions; (3) provision of data on manpower needed in the region; and (4) facilitation of participant registration. This study conducted a formative evaluation to find out the role of the subnational government in supporting the implementation of the Pre-Employment Card Program in West Java Province who holds the highest number of the Pre-Employment Card Program beneficiary in Indonesia. The data were obtained from interviews with officers of the Manpower and Transmigration Office of West Java Province, the Bandung City Manpower Office, the Social Service of West Java Province, labor union, and the Indonesian Employers' Association of West Java Province. Using the narrative analysis technique, it can be concluded that the role of subnational government in the Pre-Employment Card Program is minimal, which only acts as spectators. Of the four mandated roles, the West Java subnational government can only socialize and provide facilitation services for registration and selection of types of training. Therefore, Commission IX needs to encourage the central government to provide access and space for the subnational government to carry out its roles in order to increase the effectiveness of the implementation of the Pre-Employment Card Program. There’s also a need to encourage the subnational government to stimulate the labor market in its region to absorb graduates of the Pre-Employment Card Program training.Abstrak:Program Kartu Prakerja merupakan kebijakan responsif atas kekhawatiran sulitnya mendapatkan pekerjaan, terutama di masa pandemi. Pemda diharapkan berperan dalam (1) sosialisasi; (2) penyediaan data lembaga pelatihan; (3) penyediaan data kebutuhan tenaga kerja di daerahnya; dan (4) fasilitasi pendaftaran peserta. Penelitian ini melakukan evaluasi formatif untuk mengetahui bagaimana peran pemda dalam mendukung pelaksanaan Program Kartu Prakerja Provinsi Jawa Barat yang merupakan daerah penerima Program Kartu Prakerja tertinggi di Indonesia. Data diperoleh melalui wawancara dengan pejabat Dinas Tenaga Kerja dan Transmigrasi Provinsi Jawa Barat, Dinas Ketenagakerjaan Kota Bandung, Dinas Sosial Provinsi Jawa Barat, serikat pekerja, dan Asosiasi Pengusaha Indonesia Provinsi Jawa Barat. Dengan teknik analisis naratif, dapat disimpulkan minimnya peran pemerintah daerah (pemda) dalam Program Kartu Prakerja yang hanya bertindak sebagai penonton. Dari empat peran yang diamanatkan, pemda Jawa Barat baru dapat melakukan sosialisasi dan memberikan layanan fasilitasi pendaftaran dan pemilihan jenis pelatihan. Oleh karena itu, Komisi IX perlu mendorong pemerintah pusat untuk memberikan akses dan ruang bagi pemda untuk melaksanakan perannya sehingga dapat meningkatkan efektivitas implementasi Program Kartu Prakerja. Selain itu, pemerintah pusat juga perlu mendorong pemda menggeliatkan pasar tenaga kerja di daerahnya untuk menyerap lulusan pelatihan Program Kartu Prakerja.